Analysis Of Marketing Strategies On The Sustainability Of Micro Enterprises In The Culinary Areas Of Bandung City With Digital Transformation As A Moderating Variable - Nabiila, Tanya; Cupian, Cupian; Muizu, Wa Ode Zusnita (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2026)
Bandung City has long been recognized by tourists as a culinary paradise. In an effort to manage this potential, the Bandung City Government has established designated culinary zones to accommodate the growing number of micro-entrepreneurs in the food and beverage sector. However, micro-businesses operating in these culinary areas continue to face significant challenges, particularly in terms of business sustainability. Most entrepreneurs tend to adopt a reactive stance—relying heavily on tourist influxes—without developing well-structured strategies to grow and sustain their businesses independently. This study aims to examine the extent to which marketing strategies influence the sustainability of micro-enterprises, with digital transformation serving as a moderating variable. A quantitative research approach was employed, using path analysis with Partial Least Squares–Structural Equation Modeling (PLS-SEM). The research sample consisted of micro-entrepreneurs located in the Dipati Ukur, Japati, and Lengkong culinary areas. The analysis reveals that both marketing strategies and digital transformation have a positive and significant effect on business sustainability. Moreover, digital transformation was found to strengthen the influence of marketing strategies on the sustainability of micro-enterprises. These findings highlight the critical importance of integrating well-planned marketing strategies with digital technology adoption to foster sustainable micro-businesses amid an increasingly competitive environment.